Teaching Philosophical Thinking and Developing Leadership Skills (Al-Jabal Journal of Humanities and Applied Sciences, 2024)
This study is an attempt to focus on an important issue related to teaching philosophical thinking, in all its manifestations (creative, critical, pastoral, collaborative) and the necessity of localizing it in our educational curricula, starting from basic to university. Because it is the way to provide students with the skill of analysis, questioning, and moving the mind, and abandoning the traditional approach followed in teaching by indoctrination, and the single discourse that filled the student’s mind with ineffective stuff, and deprived him of the skills of analysis, creativity, and dialogue, without igniting the mind’s fuse to create his vision and his own cognitive identity. .Teaching philosophical thinking develops leadership skills among young people. This is because it is a constructivist, student-centered education. To give a sustainable skill for learning, and develop the sense of logic on the one hand, and the emotional side, attentive listening, eloquent speaking, and expressing ideas clearly and concisely on the other hand, and also enriches the individual’s mental faculty when making the right decision; Therefore, it is necessary to adopt learning philosophical thinking in educational curricula, in order to create a generation with leadership skills. To be leaders of the future, they realize the value of life, the values ​​of citizenship are rooted in them, and they have the insight that enables them to detect misleading news and solve problems through the lens of rationality and logic. To establish a democratic state, whose citizens enjoy full rights; To consolidate the values ​​of citizenship.
Keywords: decision making, critical thinking, teaching philosophical thinking